Strategi integrasi teori belajar dan kaitannya dengan pengembangan kurikulum Pendidikan Islam - Vivi Andriani; Iswantir Iswantir (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to analyze the dominance of the behaviorist approach in the implementation of the Islamic Education curriculum, identify the impacts of the imbalance in the application of learning theories on the quality of learning, and formulate strategies for integrating behaviorist, cognitive, constructivist, and humanistic learning theories into Islamic Education curriculum development. The study employed a qualitative approach using a library research design. Data were collected from accredited scientific journals, relevant reference books, and official curriculum documents and analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the dominance of behaviorist theory is influenced by the normative characteristics of Islamic Education content, teacher-centered instructional practices, limited pedagogical competence among teachers, and assessment systems that primarily emphasize cognitive achievement. This imbalance has resulted in limited development of students' higher-order thinking skills, active learning engagement, internalization of Islamic values, and intrinsic learning motivation. Therefore, integrating behaviorist, cognitive, constructivist, and humanistic learning theories across all curriculum components is a strategic approach to developing a holistic, contextual, and student-centered Islamic Education curriculum. Such integration is expected to produce graduates who are intellectually competent, spiritually grounded, morally upright, and capable of adapting to the challenges of the digital era.